2017
DOI: 10.1007/s00270-017-1756-4
|View full text |Cite
|
Sign up to set email alerts
|

Trans-splenic Access for Portal Venous Interventions in Children: Do Benefits Outweigh Risks?

Abstract: Trans-splenic access is a useful technique for successful pediatric portal interventions. Although it entails a substantial risk of intraperitoneal bleeding, this can be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 27 publications
2
32
0
11
Order By: Relevance
“…TIPS placement has been accepted for the prevention of variceal bleeding and management of refractory ascites. Transplenic access into the portal system for placement of intrahepatic portosystemic shunt has been increasingly used to recanalize the portal vein, and has a high success rate 70,71. Kallini et al 70 reported the placement of TIPS through the transplenic approach in five symptomatic, noncirrhotic patients with complete occlusive chronic PVT, having durable patency rate and providing symptom alleviation.…”
Section: Interventionsmentioning
confidence: 99%
“…TIPS placement has been accepted for the prevention of variceal bleeding and management of refractory ascites. Transplenic access into the portal system for placement of intrahepatic portosystemic shunt has been increasingly used to recanalize the portal vein, and has a high success rate 70,71. Kallini et al 70 reported the placement of TIPS through the transplenic approach in five symptomatic, noncirrhotic patients with complete occlusive chronic PVT, having durable patency rate and providing symptom alleviation.…”
Section: Interventionsmentioning
confidence: 99%
“…30 A higher complication rate of transsplenic access is reported, specifically a 27% complication rate (12/44 patients) due to intraperitoneal bleeding; however, all patients were managed supportively with none requiring splenectomy or splenic artery embolization. 29 Ohm et al identified a lower transsplenic complication rate of 10% (1/10). 25 Routine use gelfoam, coils, or a combination thereof, to embolize transhepatic and transsplenic access routes, is recommended.…”
Section: Treatment Outcomes and Complicationsmentioning
confidence: 97%
“…3,5,24,27 Recently, the safety and efficacy of a transsplenic approach was recognized. 25,28,29 Mechanical advantages of the trans-splenic approach are similar to transhepatic, with the additional benefit of avoiding further graft injury. Moreover, a transsplenic approach is preferred, with variant anatomy of a left lobe transplant, attenuation of intrahepatic PV branches, or cavernous transformation of the main portal vein.…”
Section: Imaging Workupmentioning
confidence: 99%
“…9a-f) demonstrated success in treating eight patients with Roux limb varices; however, intraperitoneal bleeding occurred in 27% of patients with a significant correlation between hemorrhage and intraprocedural anticoagulation. 70 The majority of published case reports and small case series of successful management of bleeding jejunal varices in adults are in patients with prior liver transplant, extrahepatic portal venous obstruction, or hepatopancreatobiliary surgery (commonly choledocojejunostomy) which suggests an altered venous collateralization pathway postprocedurally leading to varices at the jejunal anastamosis. 59,[71][72][73][74][75] There are only three cases reported of adults patients with bleeding jejunal varices without portal hypertension or prior surgery, 76 and none in the pediatric literature.…”
Section: Small Bowel and Roux Limb Varicesmentioning
confidence: 99%